Instruments for assessing loneliness in older people in Portugal: a scoping review - Carvalho, Rita Silva (2022)
Loneliness is a public health problem that has been increasing worldwide and affecting many older adults. The COVID-19 pandemic has increased the worrying levels of loneliness. The subjective nature of loneliness challenges its assessment. Assessing loneliness with validated instruments becomes crucial to characterize, diagnosis, and plan adequate interventions, at individual and community levels. Objective: To map the validated instruments for the Portuguese older population (65+ years) that assess loneliness; identify and analyze their psychometric properties and the contexts where they are used. Method: A scoping review was performed according to the JBI methodology and prepared using the PRISMA-ScR. Studies with older people (65+ years) were included, where loneliness was assessed or addressed using validated instruments in Portugal. The identification of studies was performed in seven databases.The database used for the gray literature was the RCAAP. Data were extracted and analyzed descriptively through an instrument developed and aligned with the objective and research question. The results are presented in a descriptive way. Results: 78 studies were identified, of which 24 were included in this scoping review. Four studies validated three instruments for the Portuguese older population (ULS-16, ULS-6 and SELSA-S), with results that support their validity and reliability. Twenty studies assess loneliness in Portuguese older adults, essentially reporting convergent and divergent validity data. Six studies used other instruments such as the UCLA-R and the ULS-3, without adaptation and validation data reported for the Portuguese older population. Conclusion: Three valid and reliable instruments were identified to assess the loneliness of Portuguese older people, in particular, the UCLA Loneliness Scale (16 items) which presented more robust and adequate psychometric properties. The instruments identified justify more psychometric, and methodological studies to translate, adapt and validate other instruments that assess loneliness in Portuguese older people.